2022 Electricity Profiles - United Nations Department of Economic; Social Affairs (United Nations, 2025)
The 2022 Electricity Profiles contains electricity profiles for almost 230 countries and territories, providing detailed information on production, trade and consumption of electricity, net installed capacity and thermal power plant input and efficiency for all countries.